Pengaruh Berbagai Metode dan Jenis Kelapa Terhadap Kualitas Virgin Coconut Oil (VCO) - Nikita Masirin; Maxie Djonny T.; Lydia Melawaty (Prodi Teknik Kimia, 2023)
The purpose of this study was to study the effect of the method of making VCO and the type of coconut on the quality of VCO.The benefit of this research is to provide information to the community about various ways of making virgin coconut oil to see its influence with the type of coconut used on the quality of VCO produced, economical, functional and can increase the selling value of coconut products, especially virgin coconut oil (VCO). The method of making VCO consisted of enzymatic method, fermentation method, and acidification method with ordinary coconut and hybrid coconut. Determination of quantity includes calculation of volume, yield and density while determining the quality includes water content, acid number, and organoleptic test. The research result found that the method of making VCO and the type of coconut affected the quality of VCO.